REDUCE MATERIAL BREAKAGE USING KEPNER-TREGOE TROUBLESHOOTING ANALYSIS IN LOGISTIC MANAGEMENT SYSTEMS - Rosyadi, Dzakiyyah; Wijayanti, Risna (Jurnal Management Risiko dan Keuangan, 2022)
This research study aims to discover the root cause of what could influence the number of bottle breakage in the Aqua Langkat Plant using gathered information from 20 people through purposive sampling with the characteristics of users correlating with the natural processes of bottle breakage and by direct observations through activities like Gemba Walk. The disclosure is done with descriptive research to explain the causal effects observed within the triggers listed down undergoing Kepner-Tregoe problem-solving approaches. The analysis using Situation Appraisal showed three distinctions from Langkat plant to Solok and Tanggamus plant, which affected the number of workforces, waiting time, and inspection method. Problem Analysis identified 14 abnormalities, with ten highly prioritized items and four medium prioritized items located chiefly in the loading area and warehouse. Through SCAMPER Technique, substituting the verification method and rearranging the water reuse area become the two most viable options to be implemented. With the Alternative Solutions Rating and Adverse Consequences, replacing the verification method becomes the most preferred option with the minimum risk. Preventive and contingent actions are formulated through Potential Problem Analysis to address the four undesirable situations.